Ethnobiology in the gumbregan maheso tradition of the East Javanese people, Indonesia - Birran, Regan Abadi Khalid Putra Yusac; Wahidah, Baiq Farhatul; Nisa', Galih Kholifatun (Universitas Negeri Jakarta, 2025)
The Gumbregan Maheso tradition became the main source of ethnobiological study. The tradition is related to people’s indigenous knowledge in utilizing livestock. The study aims to identify types of animals and the meaning of the gumbregan maheso ceremony in Banyubiru village, Widodaren Sub-district, Ngawi Regency, Indonesia. The research uses a qualitative descriptive method to deeply describe ethnobiological values of the Gumbregan Maheso tradition of the East Javanese people using a purposive sampling technique and snowball sampling. Data is collected through semi-structured interviews with 15 informants, consisting of traditional leaders, farmers, and communities involved in the implementation of the tradition. The research results show that the type of animals used in the Gumbrega Maheso tradition is a buffalo and ingkung chicken to serve alongside offerings, such as polo pendem, ketupat, and lepet. The ceremony is intended to express gratitude for the gift of a healthy and reproducing animal